Ultrasound-assisted extraction of protein from Bombay locusts and its impact on functional and antioxidative properties - Passakorn Kingwascharapong; Manat Chaijan; Supatra Karnjanapratum (My University, 2021)
Abstract Impact of ultrasound-assisted process (UAP) on yield, functional properties, antioxidant properties and molecular characteristics of protein extracted from Bombay locusts (BL) ( Patanga succinta L.) was studied. Different conditions of UAP were implemented for different amplitudes (40–60%) and times (10–30 min) during aqueous extraction. Notably, UAP could enhance yield and protein recovery, compared with those from typical process (TP) (continuously stirred at 100 rpm at room temperature for 1 h). UAP conditions used governed the change of surface hydrophobicity and free α-amino content of BL. UAP could improve solubility of BL, especially at pH levels higher than 2. UAP had no significant ( p > 0.05) detrimental effects on foaming capacity and stability of BL. Nevertheless, UAP, particularly at 50–60% amplitudes, affected the emulsion activity and stability of BL. UAP provided BL with high radical scavenging activities and good electron donating ability, especially that from 60% amplitude for 20 min (UAP-60/20). UAP-60/20 showed the impact on change of isoelectric point and molecular characteristic monitored by Fourier transform infrared (FTIR) of BL, compared to those from TP. In addition, BL was also an excellent source of both essential and nonessential amino acids. Therefore, UAP potentially enhanced BL extraction efficiency, resulting the BL with good functional and antioxidative properties.
Keywords: Protein Hydrolysis and Bioactive Peptides